Bony Tunnel Formation Associated with the Distal Segment of the Frontal Branch of the Middle Meningeal Artery - de Campos, Deivis; da Silveira, Caroline Haubert; Jotz, Geraldo Pereira; Malysz, Tais (Journal of Neurological Surgery Part B: Skull Base, 2019)
The knowledge of certain anatomical variations is fundamental and any surgeon who operates without that knowledge may encounter difficulty during surgery. In this context, there is the middle meningeal artery (MMA) which also engenders considerable clinical interest due to its location. The MMA is predominantly periosteal, irrigating the bone and dura mater. It enters the floor of the middle cranial fossa through the foramen spinosum, travels laterally through a middle fossa bony ridge, and curves anteriorly over the upper-greater wing of the sphenoid where it divides into parietal and frontal branches at a variable point. Occasionally, the distal segment of the frontal branch may pass through a bony tunnel of variable size. To the best of our knowledge, there is no evidence in the current literature on the incidence of this rare bony tunnel. Therefore, we decided to investigate the incidence of this bony tunnel in 85 dry skulls of adults (both genders) belonging to the didactic collection of the Human Anatomy Laboratory of the Universidade de Santa Cruz do Sul, Brazil. All the skulls were examined bilaterally for the presence or absence of the bony tunnel associated with the distal segment of the frontal branch of the MMA. Of the 85 skulls analyzed, the bony tunnel was present on the right side in 1.18% and on the left side in 5.88% (p = 0.045). Thus, in the studied sample, there was a significant tendency for this bony tunnel to be formed on the left side.
Keywords: middle meningeal artery; bony tunnel; embryology; skull